Potential applications of glucosyltransferases in terpene glucoside production: impacts on the use of aroma and fragrance - Schwab, Wilfried; Fischer, Thilo C.; Giri, Ashok; Wuest, Matthias (Applied Microbiology and Biotechnology, 2015)
The detection of glucoconjugated forms of monoterpene alcohols in rose petals in the late 1960s opened the new field of nonvolatile aroma precursors in flavor research. It is now well established that odorless glycosides represent a significant pool of aroma precursors in plants where they act as preformed but inactivated defense or attractive chemicals. Technical improvements in the separation and identification of plant secondary metabolites have provided a multitude of chemical structures, but functional characterization of glycosyltransferases that catalyze their formation lags behind. As technical efforts and costs for DNA sequencing dramatically dropped during the last decade, the number of plant genome sequences increased significantly, thus providing opportunities to functionally characterize the glycosyltransferase gene families in plants. These studies yielded the first glycosyltransferase genes that encode efficient biocatalysts for the production of monoterpene glucosides. They have applications in the food, feed, chemical, cosmetic, and pharmaceutical industries as slow release aroma chemicals.

Polymerization-incompetent uromodulin in the pregnant stroke-prone spontaneously hypertensive rat - Mary, Sheon; Small, Heather Yvonne; Siwy, Justyna; Mullen, William; Giri, Ashok; Delles, Christian (Hypertension, 2017)
The kidney is centrally involved in blood pressure regulation and undergoes extensive changes during pregnancy. Hypertension during pregnancy may result in an altered urinary peptidome that could be used to indicate new targets of therapeutic or diagnostic interest. The stroke-prone spontaneously hypertensive rat (SHRSP) is a model of maternal chronic hypertension. Capillary electrophoresis-mass spectrometry was conducted to interrogate the urinary peptidome in SHRSP and the control Wistar-Kyoto strain at three time points: prepregnancy and gestational days 12 and 18. The comparison within and between the Wistar-Kyoto and SHRSP peptidome at all time points detected 123 differentially expressed peptides (fold change >1.5; P<0.05). Sequencing of these peptides identified fragments of collagen a-chains, albumin, prothrombin, actin, serpin A3K, proepidermal growth factor, and uromodulin. Uromodulin peptides showed a pregnancy-specific alteration in SHRSP with a 7.8-fold (P<0.01) and 8.8-fold (P<0.05) increase at gestational days 12 and 18, respectively, relative to the Wistar-Kyoto. Further investigation revealed that these peptides belonged to the polymerization-inhibitory region of uromodulin. Two forms of uromodulin (polymerization competent and polymerization incompetent) were found in urine from both Wistar-Kyoto and SHRSP, where the polymerizationincompetent form was increased in a pregnancy-specific manner in SHRSP. Nifedipine-treated pregnant SHRSP showed only polymerization-competent uromodulin, indicating that calcium may be mechanistically involved in uromodulin polymerization. This study highlights, for the first time, a potential role of uromodulin and its polymerization in hypertensive pregnancy.
Keywords: Hypertension; Kidney; Nifedipine; pregnancy; uromodulin

Structural and functional analysis of UGT92G6 suggests an evolutionary link between mono- and disaccharide glycoside-forming transferases - Huang, Fong-Chin; Giri, Ashok; Daniilidis, Melina; Sun, Guangxin; Härtl, Katja; Hoffmann, Thomas; Schwab, Wilfried (Plant and Cell Physiology, 2018)
Glycosylation mediated by UDP-dependent glycosyltransferase (UGT) is one of the most common reactions for the biosynthesis of small molecule glycosides. As glycosides have various biological roles, we characterized UGT genes from grapevine (Vitis vinifera). In silico analysis of VvUGT genes that were highly expressed in leaves identified UGT92G6 which showed sequence similarity to both monosaccharide and disaccharide glucoside-forming transferases. The recombinant UGT92G6 glucosylated phenolics, among them caffeic acid, carvacrol, eugenol and raspberry ketone, and also accepted geranyl glucoside and citronellyl glucoside. Thus, UGT92G6 formed mono- and diglucosides in vitro from distinct compounds. The enzyme specificity constant Vmax/Km ratios indicated that UGT92G6 exhibited the highest specificity towards caffeic acid, producing almost equal amounts of the 3- and 4-O-glucoside. Transient overexpression of UGT92G6 in Nicotiana benthamiana leaves confirmed the production of caffeoyl glucoside; however, the level of geranyl diglucoside was not elevated upon overexpression of UGT92G6, even after co-expression of genes encoding geraniol synthase and geraniol UGT to provide sufficient precursor. Comparative sequence and 3-D structure analysis identified a sequence motif characteristic for monoglucoside-forming UGTs in UGT92G6, suggesting an evolutionary link between mono- and disaccharide glycoside UGTs. Thus, UGT92G6 functions as a mono- and diglucosyltransferase in vitro, but acts as a caffeoyl glucoside UGT in N. benthamiana.

Mechanistic insights into enzymatic catalysis by trehalase from the insect gut endosymbiont Enterobacter cloacae - Adhav, Anmol; Harne, Shrikant; Bhide, Amey; Giri, Ashok; Gayathri, Pananghat; Joshi, Rakesh (FEBS Journal, 2019)
Energy metabolism in the diamondback moth Plutella xylostella is facilitated by trehalase, an enzyme which assists in trehalose hydrolysis, from the predominant gut bacterium Enterobacter cloacae. We report the biochemical and structural characterization of recombinant trehalase from E. cloacae (Px_EclTre). Px_EclTre showed K-M of 1.47 (+/- 0.05) mm, k(cat) of 6254.72 min(-1) and V-max 0.2 (+/- 0.002) mm center dot min(-1) at 55 degrees C and acidic pH. Crystal structures of Px_EclTre were determined in the ligand-free form and bound to the inhibitor Validoxylamine A. The crystal structure of the ligand-free form, unavailable until now for any other bacterial trehalases, enabled us to delineate the conformational changes accompanying ligand binding in trehalases. Multiple salt bridges were identified that potentially facilitated closure of a hood over the substrate-binding site. A cluster of five tryptophans lined the -1 substrate-binding subsite, interacted with crucial active site residues and contributed to both trehalase activity and stability. The importance of these residues in enzyme activity was further validated by mutagenesis studies. Many of these identified residues form part of signature motifs and other conserved sequences in trehalases. The structure analysis thus led to the assignment of the functional role to these conserved residues. This information can be further explored for the design of effective inhibitors against trehalases.
Keywords: Enterobacter cloacae; Plutella xylostella; structural analysis; trehalase; validoxylamine A

Metabolomic dynamics reveals oxidative stress in spongy tissue disorder during ripening of mangifera indica l. fruit - Oak, Pranjali; Deshpande, Ashish; Giri, Ashok; Gupta, Vidya (Metabolites, 2019)
Spongy tissue disorder, a mesocarp specific malady, severely affects the flavor and pulp characters of Alphonso mango fruit reducing its consumer acceptability. Here, we investigated comparative metabolomic changes that occur during ripening in healthy and spongy tissue-affected fruits using high resolution mass spectrometric analysis. During the spongy tissue formation, 46 metabolites were identified to be differentially accumulated. These putative metabolites belong to various primary and secondary metabolic pathways potentially involved in maintaining the quality of the fruit. Analysis revealed metabolic variations in tricarboxylic acid cycle and gamma amino butyric acid shunt generating reactive oxygen species, which causes stressed conditions inside the mesocarp. Further, reduced levels of antioxidants and enzymes dissipating reactive oxygen species in mesocarp deteriorate the fruit physiology. This oxidative stress all along affects the level of amino acids, sugars and enzymes responsible for flavor generation in the fruit. Our results provide metabolic insights into spongy tissue development in ripening Alphonso mango fruit.
Keywords: gamma amino butyric acid shunt; mango metabolomics; Oxidative stress; spongy tissue disorder; tricarboxylic acid cycle

Pathways to defense metabolites and evading fruit bitterness in genus Solanum evolved through 2-oxoglutarate-dependent dioxygenases - Cardenas, Pablo D.; Sonawane, Prashant D.; Heinig, Uwe; Jozwiak, Adam; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Pliner, Margarita; Unger, Tamar; Wolf, Dalia; Ofner, Itai; Vilaprinyo, Ester; et al. (Nature Communications, 2019)
The genus Solanum comprises three food crops (potato, tomato, and eggplant), which are consumed on daily basis worldwide and also producers of notorious anti-nutritional steroidal glycoalkaloids (SGAs). Hydroxylated SGAs (i.e. leptinines) serve as precursors for leptines that act as defenses against Colorado Potato Beetle (Leptinotarsa decemlineata Say), an important pest of potato worldwide. However, SGA hydroxylating enzymes remain unknown. Here, we discover that 2-OXOGLUTARATE-DEPENDENT-DIOXYGENASE (2-ODD) enzymes catalyze SGA-hydroxylation across various Solanum species. In contrast to cultivated potato, Solanum chacoense, a widespread wild potato species, has evolved a 2-ODD enzyme leading to the formation of leptinines. Furthermore, we find a related 2-ODD in tomato that catalyzes the hydroxylation of the bitter a-tomatine to hydroxytomatine, the first committed step in the chemical shift towards downstream ripening-associated non-bitter SGAs (e.g. esculeoside A). This 2-ODD enzyme prevents bitterness in ripe tomato fruit consumed today which otherwise would remain unpleasant in taste and more toxic.

Rapid and efficient sequestration of arsenic from contaminated water using hypertolerant Bacillus L-148 sp.: a two-step process - Bagade, Aditi; Nandre, Vinod; Ghosh, Sayanti; Battu, Shateesh; Haram, Santosh; Giri, Ashok; Kodam, Kisan (Green Chemistry, 2019)
A fast, robust and green bioreactor for arsenic sequestration from contaminated water was designed. In the two-tier bioreactor, bacterial arsenite detoxification (1 mM) was carried out followed by precipitation of arsenate in 5 min. The precipitate could be used for supercapacitor applications. This bioreactor yielded arsenic free water, therefore, this method can be adopted for scale-up. The combination of hypertolerant bacteria and fast precipitation indicates the robustness of this pilot bioreactor.

Semirational design and engineering of grapevine glucosyltransferases for enhanced activity and modified product selectivity - Joshi, Rakesh; Trinkl, Johanna; Haugeneder, Annika; Haertl, Katja; Franz-Oberdorf, Katrin; Giri, Ashok; Hoffmann, Thomas; Schwab, Wilfried (Glycobiology, 2019)
Uridine diphosphate-dependent glycosyltransferases (UGTs) catalyze the transfer of a diversity of sugars to several acceptor molecules and often exhibit distinct substrate specificity. Modulation of glycosyltransferases for increased catalytic activity and altered substrate or product specificity are the key manipulations for the biotechnological use of glycosyltransferases in various biosynthetic processes. Here, we have engineered the binding pocket of three previously characterized Vitis vinifera glycosyltransferases, UGT88F12, UGT72B27 and UGT92G6, by structure-guided in silico mutagenesis to facilitate the interactions of active site residues with flavonol glucosides and thus modify substrate specificity and activity. Site-directed mutagenesis at selected sites, followed with liquid chromatography-mass spectrometry based activity assays, exhibited that mutant UGTs were altered in product selectivity and activity as compared to the wild-type enzymes. Mutant UGTs produced larger amounts of flavonol di-monosaccharide glucosides, which imply that the mutations led to structural changes that increased the volume of the binding pocket to accommodate a larger substrate and to release larger products at ease. Mutants showed increased activity and modified product specificity. Thus, structure-based systematic mutations of the amino acid residues in the binding pocket can be explored for the generation of engineered UGTs for diverse biotechnological applications.
Keywords: flavonol; Glycosyltransferase; in silico analysis; Mutagenesis; selectivity

Characterisation of hyper tolerant Bacillus firmus L-148 for arsenic oxidation - Bagade, Aditi; Nandre, Vinod; Paul, Dhiraj; Patil, Yugendra; Sharma, Nisha; Giri, Ashok; Kodam, Kisan (Environmental Pollution, 2020)
Groundwater arsenic pollution causes millions of deaths worldwide. Long term natural and anthropogenic activities have increased arsenic levels in groundwater causing higher threats of arsenic exposure. Arsenic hyper-tolerant Firmicute Bacillus firmus L-148 was isolated from arsenic limiting Lonar lake soil, which tolerated more than 3 M arsenic and could oxidize 75 mM arsenite [As(III)] in 14 days. It oxidized As(III) in presence of heavy metals and had unusual pH optima at 9.2. B. firmus L-148 was studied at the biochemical, protein, genomic and transcript level for understanding its arsenic oxidizing machinery. The proteomic and transcript analysis exhibited the presence of ars and aio operon and supported the inducible nature of ars operon. Robust, hyper-tolerant, fast As(III) oxidizing, least nutrient requiring and multi-metal resistance qualities of the strain were used in microcosm studies for bioremediation. Artificial groundwater mimicking microcosm with 75 mM As(III) was developed. Modulation of carbon source, iron and multi metals affected growth and As(III) oxidation rate. The As(III) oxidation was recorded to be 77% in 15 days in presence of sodium acetate and Fe ions. This microcosm study can be explored for bioremediation of arsenic contaminated water and followed by precipitation using other methods. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Arsenic hyper-tolerance; Lonar lake; Microcosm studies; Multi-metal resistance; Next generation sequencing

Genome wide analysis of 14-3-3 proteins in Cicer arietinum L. and identification of isoforms responsive to Fusarium oxysporum - Gurjar, Gayatri; Nimbalkar, Suhas; Giri, Ashok; Gupta, Vidya (Current Science, 2021)
In the present study, we have identified and characterized two 14-3-3 isoforms, namely isoform A and C from chickpea (Cicer arietinum L.), that might play a crucial role during disease resistance. Further, in silico analysis of these 14-3-3 proteins was accomplished, including motif identification and structure prediction from deduced amino acid sequences. Expression profiling of the two representative 14-3-3 isoforms in the roots of wilt resistant and susceptible chickpea varieties upon Fusarium oxysporum f. sp ciceri race 1 (FOC1) challenge, revealed time dependent isoform specific differential expression in induced chickpea roots upon FOC1 colonization.
Keywords: Bioinformatics; chickpea 14-3-3s; pathogen responsive; transcriptional analysis

Machine learning-based approach to determine infection status in recipients of BBV152 (Covaxin) whole-virion inactivated SARS-CoV-2 vaccine for serological surveys - Singh, Prateek; Ujjainiya, Rajat; Prakash, Satyartha; Naushin, Salwa; Sardana, Viren; Bhatheja, Nitin; Singh, Ajay Pratap; Barman, Joydeb; Kumar, Kartik; Gayali, Saurabh; Khan, Raju; Rawat, Birendra Singh; et al. (Computers in Biology and Medicine, 2022)
Data science has been an invaluable part of the COVID-19 pandemic response with multiple applications, ranging from tracking viral evolution to understanding the vaccine effectiveness. Asymptomatic breakthrough infections have been a major problem in assessing vaccine effectiveness in populations globally. Serological discrimination of vaccine response from infection has so far been limited to Spike protein vaccines since whole virion vaccines generate antibodies against all the viral proteins. Here, we show how a statistical and machine learning (ML) based approach can be used to discriminate between SARS-CoV-2 infection and immune response to an inactivated whole virion vaccine (BBV152, Covaxin). For this, we assessed serial data on antibodies against Spike and Nucleocapsid antigens, along with age, sex, number of doses taken, and days since last dose, for 1823 Covaxin recipients. An ensemble ML model, incorporating a consensus clustering approach alongside the support vector machine model, was built on 1063 samples where reliable qualifying data existed, and then applied to the entire dataset. Of 1448 self-reported negative subjects, our ensemble ML model classified 724 to be infected. For method validation, we determined the relative ability of a random subset of samples to neutralize Delta versus wild-type strain using a surrogate neutralization assay. We worked on the premise that antibodies generated by a whole virion vaccine would neutralize wild type more efficiently than delta strain. In 100 of 156 samples, where ML prediction differed from self-reported uninfected status, neutralization against Delta strain was more effective, indicating infection. We found 71.8% subjects predicted to be infected during the surge, which is concordant with the percentage of sequences classified as Delta (75.6%-80.2%) over the same period. Our approach will help in real-world vaccine effectiveness assessments where whole virion vaccines are commonly used.
Keywords: BBV152; Covaxin; COVID-19; Ensemble methods; Infection; machine learning; SARS-CoV-2

Transcriptional and translational perturbation in abiotic stress induced physiological activities and metabolic pathway networks in spongy tissue disorder of mango fruit - Oak, Pranjali; Jha, Vineet; Deshpande, Ashish; Tanpure, Rahul; Dawkar, Vishal; Mundhe, Swapnil; Ghuge, Sandeep; Prabhudesai, Shrikant; Krishanpal, Anamika; Jere, Abhay; Giri, Ashok; Gupta, Vidya (Postharvest Biology and Technology, 2022)
Spongy tissue formation is economically the most detrimental but agriculturally less focused physiological disorder in mango. `Alphonso' cultivar is highly prone to oxidative stress induced spongy tissue disorder impacting biochemical and metabolic profile, thereby affecting pulp quality and nutritional value of the fruit. In the present study, comparative analysis of spongy and healthy mesocarp tissues of `Alphonso' mango by transcriptomics using Illumina sequencing and proteomics using LC-MS approaches, respectively identified and quantified many genes and proteins in the metabolic pathways responsible for the spongy tissue development. The table green and the mid ripe stages of `Alphonso' fruit ripening were evaluated by the transcriptomic study and outcomes were validated using proteomic investigations for all the four ripening stages. Colossal amount of data including 30,582 transcripts, 10,800 gene ontologies and 387 putative proteins was generated from this analysis. Current multi-omics exploration revealed the development of abiotic stress (mainly oxidative stress) induced perturbations in various metabolic pathways and their interconnections, leading to the spongy tissue formation in mango. This further unfolded the altered cell wall degradation, ethylene and flavonoid biosynthesis, fruit ripening and flavor formation, thus hampering the fruit specific characteristics in mango with spongy tissue disorder.
Keywords: Oxidative stress; Proteome; spongy tissue disorder; Transcriptome; ` Alphonso ` mango

Comprehensive molecular and clinical investigation of approved Anti-HCV drugs repurposing against SARS-CoV-2 infection: a glaring gap between benchside and bedside medicine - Bansode, Sneha; Singh, Pawan Kumar; Tellis, Meenakshi; Chugh, Anita; Deshmukh, Narendra; Gupta, Mahesh; Verma, Savita; Giri, Ashok; Kulkarni, Mahesh; Joshi, Rakesh; Chaudhary, Dhruva (Vaccines, 2023)
The limited availability of effective treatment against SARS-CoV-2 infection is a major challenge in managing COVID-19. This scenario has augmented the need for repurposing anti-virals for COVID-19 mitigation. In this report, the anti-SARS-CoV-2 potential of anti-HCV drugs such as daclatasvir (DCV) or ledipasvir (LDP) in combination with sofosbuvir (SOF) was evaluated. The binding mode and higher affinity of these molecules with RNA-dependent-RNA-polymerase of SARS-CoV-2 were apparent by computational analysis. In vitro anti-SARS-CoV-2 activity depicted that SOF/DCV and SOF/LDP combination has IC50 of 1.8 and 2.0 mu M, respectively, comparable to remdesivir, an approved drug for COVID-19. Furthermore, the clinical trial was conducted in 183 mild COVID-19 patients for 14 days to check the efficacy and safety of SOF/DCV and SOF/LDP compared to standard of care (SOC) in a parallel-group, hybrid, individually randomized, controlled clinical study. The primary outcomes of the study suggested no significant difference in negativity after 3, 7 and 14 days in both treatments. None of the patients displayed any worsening in the disease severity, and no mortality was observed in the study. Although, the post hoc exploratory analysis indicated significant normalization of the pulse rate showed in SOF/DCV and SOF/LDP treatment vs. SOC. The current study highlights the limitations of bench side models in predicting the clinical efficacy of drugs that are planned for repurposing.
Keywords: antiviral; COVID-19; daclatasvir; ledipasvir; SARS-CoV-2; sofosbuvir

Phenylpropanoid-specific glycosyltransferases from mango and their potential role in defense - Vare, Tejas; Joshi, Rakesh; Liao, Jieren; Hoffmann, Thomas; Schwab, Wilfried; Giri, Ashok (Plant Physiology and Biochemistry, 2026)
Alphonso mango (Mangifera indica cv. Alphonso) is a cornerstone of India's fruit industry due to its distinct aroma and shelf-life characteristics. The uridine diphosphate-dependent glycosyltransferases (UGTs) play a crucial role in stabilising aroma and defense-related specialised metabolites in fruits. The present study explores the potential role of UGTs during mango ripening and Colletotrichum gloeosporioides infection. Gene expression analysis indicated that UGTs showed dynamic expression in skin and pulp during ripening. Phylogenetic analysis revealed substrate-driven divergence of UGTs, with MiUGT92A14 and MiUGT95B15 forming distinct clades associated with flavonoid glycosylation. Recombinant UGTs showed a higher preference for UDP-glucose, which is corroborated by the high accumulation of UDP-glucose during ripening. Furthermore, it was observed that MiUGT92A14 prefers phenolic acids as substrates, while MiGT95B15 shows flavonoid specificity. Spore germination assays demonstrated that both aglycones and their glycosylated derivatives suppressed early fungal morphogenesis, supporting a role for UGT-mediated glycosylation in maintaining defense-related metabolites in a bioactive yet non-toxic form during fruit ripening. Additionally, Colletotrichum gloeosporioides inhibition assays demonstrated that glycosylated products of selected UGTs exhibited equal or enhanced antifungal activity compared with their aglycone forms, indicating that glycosylation promotes the safe accumulation of antifungal compounds by reducing aglycone toxicity to the plant. These findings suggest that glycosylation of specific metabolites is a key for ripening process and to potentiate defence against fungal pathogen.
Keywords: Anthracnose; defense; Flavonoid; Glycoconjugates; Uridine diphosphate-dependent glycosyl-transferase